PEMANFAATAN LIMBAH TULANG-TULANG IKAN MENJADI PELET PAKAN IKAN UNTUK MENCIPTAKAN KAWASAN ZERO WASTE DI PANTAI BARU PANDANSIMO KABUPATEN BANTUL - Rizki Fitriyani; Arif Kusumawanto; Ria Miliati (Master in Systems Engineering, 2014)
Pantai Baru Pandansimo is one of the attraction that is currently being developed Bantul district, located in Dusun Ngentak, Poncosari, Srandakan. Besides, we can enjoyed the beach, also served a variety of seafood from dozens of culinary stands, and there is also a Fish Auction Place (TPI). The existence of dozens of culinary stands, TPI and increasing tourists will cause the issue of waste cause the accumulation of organic waste such as leftovers in culinary stands plus there is no waste management system, the waste usually just discarded, dumped and left to rot that would cause smell and would disturb of tourist.This study aimed at finding out the extent positive impact of the utilization waste leftovers from stands culinary toward Pantai Baru Pandansimo to create zero waste region so as to reduce the quantity of waste into process fish feed. Then, to find out variation of formulation fish feed that good nutritional value so that can supply nutritional requirements of fish by Pearson Square method at various combinations of fish bone meal, shrimp waste meal, and rice bran. Chemical testing by proximate analysis and physical testing on the fifth variation to finding out variations of pellets which compatible with SNI feed the fish. So, pellets from waste can be beneficial to the surrounding community.The results of the study showed that utilizing waste leftovers from stands culinary in area Pantai Baru Pandansimo into fish is able to reduce the weight of organic waste by 2-3 quintals/month so the weight of waste from stands culinary can be reduced by 39%. Based on chemical test and physical test it was found that the optimal at the pellet P4 with a protein content of 34.34% and fat by 5.74% and P5 with a protein content 34.78% and fat by 5.14%. That results have appropriate of quality requirements for SNI-01-4087-2006 catfish, SNI-01-7242-2006 tilapia and SNI 7473:2009 carp. Waste management will provide improvements in environmental hygiene in the area Pantai Baru Pandansimo by 55% and improve waste management services by 65%. Sewage treatment will provide a positive benefit as much as 80% reduce the accumulation of waste and as much as 20% to educate people about the benefits of waste management.